Perioperative Myocardial Infarction in Free Flap for Head and Neck Reconstruction. (March 2022) - Sou, Weng-Kit; Perng, Cherng-Kang; Ma, Hsu; Shih, Yu-Chung
Abstract : Introduction: Acute myocardial infarction (AMI) is a postoperative complication of major surgical procedures, including free flap surgery. It is the most common cause of postoperative morbidity and mortality. Moreover, patients receiving free flap reconstruction for the head and neck have significant risk factors such as coexisting coronary artery disease (CAD). Our primary aim was to ascertain predictors of perioperative AMI to enable early detection and consequently early treatment of perioperative AMI. Our secondary aim was to determine the group of patients who would be at a high risk for perioperative AMI after free flap surgery. Materials and Methods: This retrospective study enrolled patients who underwent free flap reconstruction surgery at the Division of Plastic and Reconstructive Surgery of Taipei Veterans General Hospital between 2013-01 and 2017-12. Results: This study included 444 patients and 481 free flap head and neck reconstruction surgeries. Fifteen (3.1%) patients were diagnosed with perioperative AMI. Statistical analysis of the variables revealed that patients with underlying CAD or cerebrovascular accident (CVA) were at a high risk of developing perioperative AMI (odds ratio: 6.89 and 11.11, respectively). The flap failure rate was also higher in patients with perioperative AMI compared with those without perioperative AMI ( P = 0.015). Conclusions: Patients with underlying diseases, such as CAD or CVA, constituted high-risk groups for perioperative AMI.